The influence of extrinsic motivating factors on employees’ work performance at banking sectors in Malaysia: The mediating effect of psychological ownership - Ravesangar, Kamalesh; Fauzi, M. A. (Universiti Malaysia Sarawak, 2022)
This study investigates the influences of extrinsic motivating factors on employees' work performance in banking sectors in Malaysia when the psychological ownership act as mediating effect existed. Generally, this study analyses three independent variables, categorized as extrinsic (working condition, job security, and company policy) motivating factors on the dependent variable of employees' work performance when psychological ownership acts as a mediating effect in banking sectors in Malaysia. This study was conducted to determine employee work performance issues, namely, poor service quality, poor communication, high employee turnover, and work-related stress in Malaysian banking sectors. The research tools used in this study were personal distribution and online mail questionnaires. A total of 3700 frontline employees were selected for the questionnaire, but only 370 respondents are fit for further analysis. The survey data was gathered within a one-month duration. The findings revealed that work conditions and company policy have a significant favourable influence on psychological ownership. The following results show that psychological ownership positively mediates the relationship between company policy and work conditions with work performance. A theoretical framework has been constructed based on Herzberg's Theory of hygiene factors used in this research. The outcome of this study would help bank management introduce practical strategies for improving the employees' work performance which leads to business growth.